Hairpin-end conformation of adeno-associated virus genome determines interactions with DNA-repair pathways - Cataldi, M P; McCarty, D M (Gene therapy, 2013)
The palindromic terminal repeats (TRs) of adeno-associated virus (AAV) form DNA hairpins (HPs) are essential for replication and for priming the conversion of single-stranded virion DNA to double strand. In recombinant AAV (rAAV) gene-delivery vectors, they are targets for the DNA-repair pathways leading to circularization, concatemerization and, infrequently, chromosomal integration. We investigated the effect of the TR HP on recombination by comparing specific DNA substrates transfected into wild-type and DNA-repair-deficient cells. DNA molecules with the TR sequences constrained in the T-shaped HP conformation at one or both ends were subject to a loss of gene expression, which was partially relieved in ataxia telangiectasia mutated (ATM −/− ) cells. The ATM-dependent effect was mediated by transcriptional silencing of a subset of HP-containing molecules in cis rather than a loss of DNA, and was dependent on the specific T-shaped structure of the HP and not the primary sequence. DNA molecules with simple U-shaped HP ends were unaffected by ATM-dependent silencing. The silenced molecules remained in a linear conformation, in contrast to the expressed molecules, which were circularized. In the absence of ATM activity, this subset remained linear but was actively expressed. DNA molecules with the TR sequence in the open duplex conformation, or without TR sequences, were unaffected by ATM mutation and were predominantly converted to circular forms. A separate HP-specific effect in normal cells resulted in a loss of DNA substrate in the nucleus and was ATM independent. These results suggest that the presence of the HP structure on rAAV vector genomes subjects them to specific, and sometimes unproductive, DNA-repair/recombination pathways.